A probabilistic-based approach for predicting mould growth in timber building envelopes: Comparison of three mould models. (October 2017) - Gradeci, Klodian; Labonnote, Nathalie; Time, Berit; Köhler, Jochen
Abstract: This paper applies a probabilistic-based approach as a methodology to analyze and compare the mould growth computations' results from three different mould models. This approach, instead of the conventional deterministic ones, offers the advantage of accounting for uncertainties concerning prediction of mould growth. The results are able to demonstrate more realistic and conclusive outcomes that can be applicable to real-life situations.